P74 Understanding the impetus for major systems change: a multiple case study of decisions and non-decisions to reconfigure emergency and urgent care services. (3rd September 2019) - McHugh, S; Droog, E; Foley, C; Boyce, M; Healy, O; Browne, J
Abstract : Background: The optimal organisation of emergency and urgent care services (EUCS) is a perennial problem internationally. Similar to other countries, the Health Service Executive in Ireland pursued EUCS reconfiguration in response to quality and safety concerns, unsustainable costs and workforce issues. However, the implementation of reconfiguration has been inconsistent at a regional level. Our aim was to identify the factors that led to this inconsistency. Methods: Using a multiple case study design, case study regions were selected based on the extent of emergency department reconfiguration in the region (categorised as full, partial and little/no reconfiguration). Semi-structured interviews were conducted with a purposive sample of stakeholders who were centrally involved in the reconfiguration process in each region. Interview data were supplemented with documentary analysis of proposals for EUCS in each region. Data were analysed using a framework approach, drawing on an existing conceptual framework for major system change. Cross-case analysis was conducted iteratively to identify patterns and differences across the regions. Results: Six regions were selected for analysis and 42 interviews were analysed. The impetus to reconfigure ED services was triggered by patient safety events, and to a lesser extent by having a region-specific plan and an obvious starting point for changes. However, the complexity of the next steps and political influence impeded reconfiguration in several regions. Implementation was more strategic in regions that reconfigured later, facilitated by clinical leadership and 'lead-in time' to plan and sell changes. Conclusion: While the global shift towards centralisation of EUCS is driven by universal challenges, decisions about when, where and how much to implement are influenced by local drivers including context, people and politics. This can contribute to a public perception of inequity and distrust in proposals for major systems change.